Quality of life in women with breast cancer who visit the Oncology Department of the Hospital Nacional Daniel Alcides Carrión. Callao – 2018 - Olivares-Taipe, Paulo (2019)
Objective: To determine the quality of life in women with breast cancer who visit the Oncology Department of the Hospital Nacional Daniel Alcides Carrión (Callao). Materials and methods: This study had a basic, observational, descriptive, prospective and cross-sectional design. The sample consisted of 100 patients with breast cancer who visited the hospital between May and July 2018. The data collection instrument was a 34-item questionnaire. Results: Most women with this disease had a fair quality of life (93 %). In the physical and psychological dimensions, most of them also presented a fair quality of life (98 % and 87 %, respectively) and, in the social dimension, they showed a poor quality of life (77 %). Conclusions: These women experienced problems in different parts of their body. In the psychological dimension, they presented an unhealthy quality of life generating a sense of uneasiness and anxiety. In the social dimension, they also presented a poor quality of life resulting in little participation in social gatherings and recreational visits, and a rift from friends and family.